PIH18 Cost-Effectiveness Of 13-Valent Pneumococcal Conjugate Vaccination In Kazakhstan - Bektur, C; Nurgozhin, T (Value in Health, 2015)
The aim of the study was to investigate the cost-effectiveness of 13-valent pneumococcal conjugate vaccine (PCV-13) programme for children in Kazakhstan from the perspective of Ministry of Health.